Challenges of Fuel Subsidy Removal on the Nigerian Economy: A Study of Gombe State - Abdulyakeen , Abdulrasheed; Mumuni, Nurain Abayomi (Kashere Journal of Politics and International Relations, 2024)
The study examines the Implications of Fuel Subsidy Removal on the Nigerian Economy. A Study of Gombe State using traditional economic theory as theoretical framework. While adopting survey design, questionnaires were used as an instrument for the collection of data. The study revealed that, it has increased inflation by 50% and decreased economic welfare. In turn, this resulted in inflation and a decline in consumer purchasing power. Furthermore, the results showed that the citizens of Gombe state have a bad opinion of the subsidies that were eliminated. In addition, the elimination of the fuel subsidies raised transportation fares by 35%. They no longer have greater commercial opportunities as a result of the elimination of gasoline subsidies. The study conclude that the elimination of gasoline subsidies has no beneficial effects on Nigeria’s economy, government should remove subsidies in a sincere manner, or else the public will be willing to reject any programs, no matter how beneficial, that are planned. Before drafting or implementing any policies, the government should also ensure that the relevant parties have been consulted, particularly when the policies directly affect people, both in rural and urban areas.